Peningkatan Kompetensi Rias Wajah Pada Guru Tata Busana di Forum MGMP Kabupaten Semarang - Nurulisma Saputri; Kuswidyaningrum N. J (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
MGMP Fashion Forum is a forum for sharing information but can also be a forum to improve teachers' knowledge and skills. Fashion Vocational School teachers are one of those whose knowledge and skills can be developed, not only in the field of fashion. Fashion teachers can also be given knowledge related to makeup. Because fashion and makeup are something that is related to support person's appearance. Based a request from the Semarang Regency Fashion MGMP Forum to AKS Kartini Semarang provide training. A community service was held at SMKN 1 Jambu. The knowledge given fashion teachers is basic makeup knowledge and skills, namely natural flawess makeup. Purpose of service is that teachers under the auspices of MGMP Fashion Design Semarang Regency are expected have knowledge and skills, especially makeup,both themselves and for activities Fashion show makeup for students. Method of carrying out activity carried out in several stages including preparation stage, the implementation stage, asking questions and closing. Activity was carried out in the form lectures, demonstrations and questions and answers which attended 21 members of the MGPM Fashion Teacher Forum Semarang Regency. The material presented was in the form of flawless makeup. Implementation of the activity went smoothly,